Peningkatan Infrastruktur Desa Melalui Pemanfaatan Limbah Domestik Sebagai Campuran Batu Bata - Varella, Mima -; Nasihah, Mima - (Jurnal EnviScience (Environment Science), 2020)
Near the gate enter Sugiwaras Village, Sumberjo Hamlet, Kalitengah District, Lamongan Regency, many kinds of inorganic domestic waste such as bottles, plastics, cans and others. The rubbish is just thrown away and left in a landfill without any separation between dry rubbish and solid rubbish. Waste that is not well managed will produce a negative impact on the environment which will result in pollution both on land, water, and in the air. The purpose of this study is to reduce environmental pollution by utilizing plastic waste as a mixture of bricks. To get bricks products through plastic waste treatment and to find out the best composition of bricks, a research about the nature of plastic waste is needed so that it can be processed into a bricks with the right comparison. The method used in this study is the Lego method which is usually used by children’s games, as a way of answering problems in the area of Sugiwaras Village. And for the research variables we use two research variables, namely: 1. Independent variables, 2. Dependent variables. The results of this study are that Domestic Waste Bricks (BABALIDO) products can be used to help improve infrastructure development in the village.